Stress partitioning of the phases and microstructural evolution in cast Al-8.3Zn-4.3Mg-0.8Mn alloys with different Fe contents - Chen, Jingsi; Zhao, Yuliang; Tang, Chuanyao; Liu, Le-hua; Song, Dongfu; Zhang, Weiwen (Journal of alloys and compounds, 2025)
Recycled aluminum alloys typically contain various secondary phases, whose effects on mechanical properties are not clearly understood. This study utilized synchrotron radiation X-ray imaging and diffraction techniques, along with transmission electron microscope, to systematically investigate the microstructural evolution and the stress partitioning of different phases of Al-Zn-Mg alloys with varying Fe contents and strains. The results indicate that the primary Al6(Fe,Mn) appeared, and the 3D morphology changes from Chinese script-like to interconnected lath-like structure as the Fe content increased from 0.1 % to 1.0 %. Simultaneously, the addition of Fe led to increased yield strength (YS) but decreased ductility. Deformation mechanism studies revealed that the increase of YS was caused by strong stress partitioning characteristic of Al6(Fe,Mn). When the alloy fractured, Al6(Fe,Mn) phase bears the stress about 827 MPa, which is approximately 540 MPa higher than that of α-Al. However, the premature failure of the lath-like Al6(Fe,Mn) at a strain of 1.0 % was the main cause of subsequent brittle fracture of the alloy, which had limited the potential increase in alloy strength from higher volume fraction of Al6(Fe,Mn) phases. This work not only provides new insights into the deformation mechanisms of aluminum alloys with high Fe content but also offers new ideas for the design of microstructures and compositions in recycled alloys. •3D morphology of Al6(FeMn) changed from Chines script-like to lath-like structure.•Strong stress partitioning characteristic of Al6(Fe,Mn) causes the increase of YS.•Synchrotron radiation XRD showing the fracture of the Al6(Fe,Mn) at the stain of 1 %.•The premature failure of the Al6(Fe,Mn) causes the brittle fracture of the alloy.